2018
DOI: 10.3389/fchem.2018.00261
|View full text |Cite
|
Sign up to set email alerts
|

A Plasma Biochemical Analysis of Acute Lead Poisoning in a Rat Model by Chemometrics-Based Fourier Transform Infrared Spectroscopy: An Exploratory Study

Abstract: In this work, we explored to use chemometrics-based Fourier transform infrared (FTIR) spectroscopy to investigate the plasma biochemical changes due to acute lead poisoning (ALP) in a rat model. We first collected the FTIR spectra of the plasma samples from the rats with and without suffering from ALP. We then performed the chemometric analysis of these FTIR spectra using principal component analysis (PCA) and partial least squares discriminant analysis (PLS-DA). We found that the chemometrics-based FTIR spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…[ 10 ] As reported by previous studies, elevated blood lead concentration is associated with hematologic findings such as BS of red cells and hemolytic anemia, and it has been proven that decreased P5N activity is partially responsible for these findings. [ 10 11 ] Also, high blood lead level (BLL) could damage the majority of soft tissues mainly the liver. [ 10 ] The central role of hepatic tissue in detoxification emphasizes the importance of liver function in clearance of xenobiotics especially in drug-addicted individuals.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…[ 10 ] As reported by previous studies, elevated blood lead concentration is associated with hematologic findings such as BS of red cells and hemolytic anemia, and it has been proven that decreased P5N activity is partially responsible for these findings. [ 10 11 ] Also, high blood lead level (BLL) could damage the majority of soft tissues mainly the liver. [ 10 ] The central role of hepatic tissue in detoxification emphasizes the importance of liver function in clearance of xenobiotics especially in drug-addicted individuals.…”
Section: Introductionmentioning
confidence: 82%
“…[ 9 ] In fact, lead intoxication shares some features with hereditary P5N deficiency. [ 10 ] As reported by previous studies, elevated blood lead concentration is associated with hematologic findings such as BS of red cells and hemolytic anemia, and it has been proven that decreased P5N activity is partially responsible for these findings. [ 10 11 ] Also, high blood lead level (BLL) could damage the majority of soft tissues mainly the liver.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…The model of acute lead poisoning is established by giving experimental animals a single administration of a lead compound ( 27 ) whereas establishment of the model of chronic lead poisoning involves multiple administrations of a lead compound ( 28 ).Rats were divided in random to groups (five rats/group). The rat model of chronic lead poisoning was established by daily intragastric Pb(Ac) 2 injections at a high dosage of 20 mg/kg body weight for 1 week, and also at a low dosage (5 mg/kg body weight) of Pb(Ac) 2 solution for 30 days after a recovery period of 3 days.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with the most advanced X-ray fluorescence technology, the detection limit, detection speed, and detection accuracy of CO 2 laser-induced spectroscopy are comparable, and the hardware of CO 2 laser-induced spectroscopy has a lower price and is expected to replace X-ray fluorescence spectroscopy to realize the detection of lead in glass. Tian et al [52] used Fourier transform infrared spectroscopy based on principal component analysis (PCA) and partial least squares (PLS-DA) to study the biochemical changes in plasma during acute lead poisoning (ALP) in rats. The researchers first collected a large number of plasma samples from rats with and without ALP and found that the corresponding biochemical changes between plasma and lead can be used as potential spectral biomarkers for the diagnosis of lead poisoning.…”
Section: Spectrometrymentioning
confidence: 99%